2019
DOI: 10.1186/s12870-019-1646-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and iTRAQ-based proteomic analyses reveal the function of exogenous γ-aminobutyric acid (GABA) in improving tea plant (Camellia sinensis L.) tolerance at cold temperature

Abstract: BackgroundInternal γ-Aminobutyric Acid (GABA) interacting with stress response substances may be involved in the regulation of differentially abundant proteins (DAPs) associated with optimum temperature and cold stress in tea plants (Camellia sinensis (L.) O. Kuntze).ResultsTea plants supplied with or without 5.0 mM GABA were subjected to optimum or cold temperatures in this study. The increased GABA level induced by exogenous GABA altered levels of stress response substances – such as glutamate, polyamines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 83 publications
2
38
0
Order By: Relevance
“…Synthesis of cyoprotectant molecules, increase in tissue-specific scavenging capacity against excessive ROSs, decrease in malondialdehyde content, and production of nitrogenous compounds with low molecular weight are some conspicuous examples of protective/defensive mechanisms involved in minimizing the deleterious effects of stressing agents in plants. In response to environmental anxiety, plants start accumulating GABA in their affected tissues quickly which help them adapting stress conditions to some extent [14]. Intensive studies in the recent past have demonstrated that endogenous levels of GABA can remarkeably be increased by exogenous application of GABA [39,40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of cyoprotectant molecules, increase in tissue-specific scavenging capacity against excessive ROSs, decrease in malondialdehyde content, and production of nitrogenous compounds with low molecular weight are some conspicuous examples of protective/defensive mechanisms involved in minimizing the deleterious effects of stressing agents in plants. In response to environmental anxiety, plants start accumulating GABA in their affected tissues quickly which help them adapting stress conditions to some extent [14]. Intensive studies in the recent past have demonstrated that endogenous levels of GABA can remarkeably be increased by exogenous application of GABA [39,40].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to playing an important role in amino acid transport model, various types of proteins help in producing stress response substances and are directly or indirectly involved in the related metabolic pathways. Zhu et al [14] identified thirty-six (36) proteins involved in amino acid transport system in tea plant (Camellia sinesis L.). Any damage to the structure of proteins, either due to stress or other harmful agent, may compromise tissue-specific cellular integrity of plants [77].…”
Section: Plant Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was generally caused by the faster rate of anthocyanin degradation compared with its biosynthesis rate in strawberry. Exogenous GABA treatment has been reported to induce anthocyanins accumulation in plants (Zhu et al, 2019). This might explain why the F44/GadB1C1 group showed the slightest change of C-value.…”
Section: Effect Of F44/gadb1c1 Fermentation Product On Strawberry Rotmentioning
confidence: 93%
“…Furthermore, GABA can alleviate oxidative damage of fruits (Yang et al, 2011;Li et al, 2019) and barley seedlings (Song et al, 2010) through enhancing the activities of antioxidant enzymes. Exogenous GABA treatment significantly improves the storage performance of fruits through increasing the accumulation of citrate and amino acids (Sheng et al, 2017), reducing chilling injury (Shang et al, 2011), and altering the carbon and nitrogen metabolism (Zhu et al, 2019). Therefore, GABA has great potential as an antioxidant or additive in food preservation.…”
Section: Introductionmentioning
confidence: 99%